2019
DOI: 10.5539/ijel.v10n1p37
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Vocabulary Knowledge and FL Speaking Performance

Abstract: Research has highlighted the importance of vocabulary learning in order for L2 learners to cope with the linguistic demands of fundamental skills such as reading and listening. However, few empirical studies have investigated the relative strength of the association of a specific construct of vocabulary knowledge has on the skill of speaking. To understand more fully the practical implications of such a relationship, this paper presents empirical evidence gathered to explore a measure of productive vocabulary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…It is important to note that the greater learning gain was of receptive vocabulary knowledge. The rather more limited learning gain of productive vocabulary knowledge seems to be attributable to the limited exposure to spoken input in classrooms (Alharthi, 2020;DeHaan, Reed, & Kuwanda, 2010;Nation, 2001). This suggests that even though watching English subtitled movies may be enjoyable and involve a rich vocabulary to learn from, participants" production of the form-meaning link requires a kind of deep processing that they are not likely to be able to perform while giving attention to interesting, even exciting aural input from a dramatic movie.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the greater learning gain was of receptive vocabulary knowledge. The rather more limited learning gain of productive vocabulary knowledge seems to be attributable to the limited exposure to spoken input in classrooms (Alharthi, 2020;DeHaan, Reed, & Kuwanda, 2010;Nation, 2001). This suggests that even though watching English subtitled movies may be enjoyable and involve a rich vocabulary to learn from, participants" production of the form-meaning link requires a kind of deep processing that they are not likely to be able to perform while giving attention to interesting, even exciting aural input from a dramatic movie.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the productive lexicon grades correlated moderately with L2 fluency (r = 0.34) and low correlation with comprehensibility (r = 0.27) but a slight correlation with an accent (r = 0.03). Finally, Alharthi (2020), interviewing 18 Saudi Arabia sophomore university learners of English, investigated the degree to which productive lexical knowledge correlates with and predicts speaking ability. The results demonstrated that the correlation order of different lexical frequency levels with speaking is 3,000word level (r = 0.58), 2,000-word level (r = 0.49), 5,000-word level (r = 0.39), academic word level (r = 0.30) and 10,000-word level (r = 0.23) on the interview task, showing that productive vocabulary has the most significant effect on learners with 3000word frequency level.…”
Section: Vocabulary Knowledge and Speaking Proficiencymentioning
confidence: 99%
“…Therefore, studying the association between lexical knowledge and language capability has attracted global attention. Over the past 20 years, many scholars have paid close attention to the association between lexis and reading (Cheng & Matthews, 2018;Li & Kirby, 2015;Nation, 2001;Qian, 1999Qian, , 2002 and listening (Cheng & Matthews, 2018;Matthews, 2018;Nation, 2001;Staehr, 2008Staehr, , 2009, and writing (Choi, 2017;Kilic, 2019;Olinghouse & Wilson, 2013;Webb, 2005) while a few researchers focused on the correlation between lexis and speaking ability (Alharthi, 2020;Koizumi & In'name, 2013;Uchihara & Saito, 2019). Further, few studies have ascertained the correlation between lexis and speaking in a Chinese setting.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of these two dimensions of vocabulary knowledge led to the development of some reliable and valid tests to measure them. Vocabulary size, in particular, has attracted more attention in L2 vocabulary research (David, 2008) due to its critical and substantial contribution to effective language use (Alharthi, 2020;Dabbagh & Janebi Enayat, 2019;Derakhshan & Janebi Enayat, 2020;Nguyen & Nation, 2011;Uchihara & Clenton, 2020). Various instruments have been, therefore, developed to examine the L2 learners' vocabulary size.…”
Section: Introductionmentioning
confidence: 99%